Educational Interaction Patterns of Students in Blended Learning during Covid 19 - Lisa Retnasari; Yayuk HIdayah; Tia Widyaningrum; Anif Istianah; Meiwatizal Trihastuti (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2022)
Abstract: The Covid 19 pandemic requires teachers to apply blended learning. This raises several patterns of interaction between teachers and students and various potentials that support and hinder them. This study aims to understand the patterns of educational interaction in blended learning at SDN 210/X Bandar Jaya during the pandemic as well as the obstacles and support in interaction patterns. This research method is descriptive qualitative. Data were obtained from school principals and teachers. Data collection techniques used are observation, interviews and documentation. Data analysis techniques used are data reduction, data display and data verification. The results of this study indicate that there are three types of interaction patterns in blended learning at SDN 210/X Bandar Jaya, namely one-way interaction that occurs when the teacher uses the lecture method, two-way interaction that occurs when the teacher uses the combined lecture method with question and answer, and interaction three directions that occur when the teacher uses the discussion method. The supporting factors for educational interaction patterns consist of teachers, facilities and infrastructure, and educational staff, while the inhibiting factors for educational interactions consist of teachers, internet networks, and passive students.Keywords: Educative Interaction, Blended learning, Covid 19 PandemicÂ Â Abstrak: Pandemi Covid 19 mengharuskan guru menerapkan pembelajaran blended learning. Hal ini memunculkan beberapa pola interaksi antara guru dan peserta didik dan berbagai potensi yang mendukung dan menghambatnya. Penelitian ini bertujuan untuk memahami pola interaksi edukatif dalam pembelajara blended learning di SDN 210/X Bandar Jaya pada masa pandemi serta hambatan dan dukungan dalam pola interaksi. Metode penelitian ini adalah kualitatif deskriptif. Data didapatkan dari kepala sekolah dan guru. Teknik pengumpulan data yang digunakan yaitu observasi, wawancara dan dokumentasi. Teknik analisis data yang digunakan yaitu reduksi data, display data dan verifikasi data. Hasil penelitian ini menunjukkan bahwa terdapat tiga jenis pola interaksi dalam pembelajaran blended learning di SDN 210/XÂ Bandar Jaya yaitu interaksi satu arah yang terjadi ketika guru menggunakan metode ceramah, interaksi dua arah yang terjadi ketika guru menggunakan metode gabungan ceramah dengan tanya jawab, dan interaksi tiga arah yang terjadi ketika guru menggunakan metode diskusi. Faktor pendukung pola interaksi edukatif terdiri dari guru, sarana dan prasarana, dan tenaga kependidikan, sedangkan faktor penghambat interaksi edukatif terdiri dari guru, jaringan internet, dan pasifnya peserta didik.Kata kunci: Interaksi Edukatif, Blended learning, Pandemi Covid 19